Answer:
the answer is A
Step-by-step explanation:
that is not correct
Answer:
C (The lower left one)
Step-by-step explanation:
I saw that the vertex was equal to (-1,1) and that is the only answer that makes sense
4/6
4/6 = 2/3
4/6 = 8/12
Answer : 2/3 and 8/12
<span>=<span><span><span><span><span>(3)</span><span>(x)</span></span>+<span><span>(3)</span><span>(4)</span></span></span>+<span><span>(2)</span><span>(<span>5x</span>)</span></span></span>+<span><span>(2)</span><span>(2)
</span></span></span></span><span>=<span><span><span><span>3x</span>+12</span>+<span>10x</span></span>+<span>4
</span></span></span><span>=<span><span><span><span>3x</span>+12</span>+<span>10x</span></span>+4
</span></span><span>=<span><span>(<span><span>3x</span>+<span>10x</span></span>)</span>+<span>(<span>12+4</span>)
</span></span></span><span>=<span><span>13x</span>+<span>16
Answer = </span></span></span><span>13x</span>+<span>16
(hope this helps)</span>